Emotional intelligence and its importance in human life – case study - Kupcewicz, Ewa; Kupcewicz, Adam (Journal of Education, Health and Sport, 2017)
Introduction. Emotional intelligence is a set of abilities used for processing emotional informations that underpins the development of social and emotional competence. Knowing one’s own emotional intelligence is a valuable element of the individual’s self-knowledge which allows to develop further and improve weaknesses through social training. Aim of the study. To study the profile of emotional intelligence and to identify the developmental needs of the researched man. Case report. The study was conducted on a 33 year old man, a computer scientist with 11 years of work experience. A qualitative research methodology was used - a case study. The Popular Emotional Intelligence Questionnaire was used to determine the overall level of emotional intelligence and its four components. The results of the study are presented with reference to sten standards. With a probability of 85%, the true test result for an overall level of emotional intelligence is in the range of 7 to 8 and can be considered as at least average and possibly even high. The researched man achieved high scores on emotional scales (from 8 to 10) and emotional control (from 7 to 10), with slightly lower scores on emotional acceptance scales (6 to 9 stens) and empathy (5 to 8 stens). The results of the strategic emotional intelligence components are statistically significantly higher than the experimental emotional intelligence components. Conclusions. Obtained results indicate that the studied man has at least average, perhaps even high general level of emotional intelligence and the predominance of strategic emotional intelligence over experimental emotional intelligence.